PENGENDALI PEMAKAIAN LISTRIK PADA PENGGUNAAN PERALATAN LISTRIK RUMAH TANGGA DENGAN MIKROKONTROLER ATMEGA8535 - , JUMARAS SITUNGKIR; , Ir. Sri Lestari, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of electrical energy for domestic use is one of the largest electric energy use in Indonesia. Electronic equipment is equipment that requires electrical energy . Therefore, along with the increasing need for the use of electrical energy we need a tool that can protect electronic equipment from fire hazards resulting from excessive electrical energy consumption resulting in a short circuit that would cause a fire . Current sensor type ACS712ELCTR-05B-T will read electrical current flowing and produces a voltage of 2,5 VDC - 4,88VDC. With a reference voltage generated by ACS712ELCTR-05B-T, it can be used as a controller or current limiting. This tool works by rising electric current passing through the current sensor ACS712ELCTR-05B-T resulting from the use of home electronics . This tool is able to limit the use of electric current which is used as a controller with relay circuit . While electricity consumption is used to display the LCD circuit .